Anthropological analysis of the late Roman cemetery at Vrajk in Gorenji Mokronog - Leben-Seljak, Petra (Arheološki vestnik, 2003)
The results are presented of the anthropological analysisof 17 skeletons from the partly excavated cemetery in GorenjiMokronog (6th-7th centuries). The mortality structure of theskeleton series, the high proportion of dental caries, and theresults of the paleopathological analyses indicate the relativelyhigh living standard of the population of this period. The morpho-logical analysis confirms the presence of an indigenous populationwith a small proportion of foreign ethnic elements and togetherwith the results of analysis of the epigenetic markers indicatespossible kinship relations in the framework of the series.